The Right Concept and Application of Polygamous Marriage in Malaysia: An Analysis to the Role of Court under the Provision of Islamic Family Law (Federal Territories) Act 1984 - Awang, Nurulbahiah (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2024)
Polygamy can be practised among Muslim in Malaysia according to certain requirements under Islamic Family Law of each States. Misconception of polygamous marriage leads to misapplication of polygamy by marriage abroad, syndicate polygamy, and anti-polygamy. This research aims to explain the right concept of polygamous marriage in socio-legal context of Malaysia. This research is a descriptive study based on the previous research on socio-legal context of polygamous marriage in Malaysia and the role of Shariah Court in deciding polygamy application under Section 23 of IFLA. This research analyses the provision under Section 23 of Islamic Family Law (Federal Territories) Act 1984 (referred as IFLA) on the power of Shariah Court in the application of polygamy with decided cases. This research found that according to Section 23 of IFLA, polygamous marriage in Malaysia is permissible but not an individual right of man. It is a public right given by the State through Shariah Court. Polygamy without Court permission is an offence and could affect the life after marriage. The Court has to decide the application of polygamous marriage based on public interest rather than individual interest to preserve the welfare of all parties involved. Therefore, this demonstrates that the procedure for polygamy in Malaysia is more bureaucratic compared to neighboring countries, such as Indonesia. This complexity is strongly guarenteed by penalty under Section 123. [Poligami dapat dilakukan di kalangan Muslim di Malaysia sesuai dengan persyaratan tertentu di bawah Undang-Undang Keluarga Islam di setiap Negara Bagian. Kesalahpahaman tentang pernikahan poligami menyebabkan penyalahgunaan poligami melalui pernikahan di luar negeri, sindikat poligami, dan anti-poligami. Penelitian ini bertujuan untuk menjelaskan konsep yang benar tentang pernikahan poligami dalam konteks sosio-legal di Malaysia. Penelitian ini adalah studi deskriptif berdasarkan penelitian sebelumnya tentang konteks sosio-legal pernikahan poligami di Malaysia dan peran Mahkamah Syariah dalam memutuskan permohonan poligami di bawah Pasal 23 IFLA. Penelitian ini menganalisis ketentuan di bawah Pasal 23 Undang-Undang Keluarga Islam (Wilayah Persekutuan) Tahun 1984 (disebut sebagai IFLA) tentang kekuasaan Mahkamah Syariah dalam penerapan poligami dengan kasus-kasus yang telah diputuskan. Penelitian ini menemukan bahwa menurut Pasal 23 IFLA, pernikahan poligami di Malaysia diperbolehkan tetapi bukan merupakan hak individu pria. Ini adalah hak publik yang diberikan oleh Negara melalui Mahkamah Syariah. Poligami tanpa izin Mahkamah adalah pelanggaran dan dapat mempengaruhi kehidupan setelah pernikahan. Mahkamah harus memutuskan permohonan pernikahan poligami berdasarkan kepentingan umum daripada kepentingan individu untuk menjaga kesejahteraan semua pihak yang terlibat. Oleh karena itu, itu membuktikan bahwa prosedur untuk poligami di Malaysia lebih birokratis dibandingkan dengan negara-negara sekitarnya, seperti Indonesia. Kompleksitas ini dijamin pula dengan ancaman hukuman berdasarkan Pasal 123.]